Screening of Sterculia guttata Seeds alongwith Extraction and Characterization of Seed Oil - KATADE, SUSHAMA; DESHMUKH, MADHAVI; PHALGUNE, USHA; BISWAS, SUJATA; DESHPANDE, NIRMALA (Asian Journal of Chemistry, 2010)
The present study describes the preliminary study of seeds of Sterculia guttata with extraction and characterization of seed oil. In preliminary study, screening of seeds by phytochemical tests, cold solvent extractions of non-polar, semi-polar and polar solvent, volatile matter, moisture content and steam distillation experiments were carried out. The oil was extracted using soxhlet apparatus and was found that S. guttata seed were rich in oil content, which was 37.74% by weight. Some of the physical and chemical characteristics of the oil such as acid value, saponification value, unsaponifiable matter, specific gravity, iodine value, viscosity, refractive index and peroxide value were determined. The values of theses parameters were compared with some most common vegetable oil. The results showed that Sterculia guttata seed oil is not edible oil.